2014
DOI: 10.1016/j.carbon.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visible light and electrode wetting on the capacitive performance of S- and N-doped nanoporous carbons: Importance of surface chemistry

Abstract: Importance of surface chemistry. Carbon, 78, Additional Information:• This paper was accepted for publication in the journal Car- AbstractNanoporous carbons with graphitic domains were synthesized from a polymer containing sulfur and nitrogen. The materials were characterized using adsorption of nitrogen, potentiometric titration TA/MS, XPS, TEM and XRD. Then they were tested as supercapacitors in threeelectrode cell and under visible light irradiation after extensive wetting either in water or a sulfuric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 58 publications
0
59
1
Order By: Relevance
“…4a), -700 (Fig. S4a †), and -800 ( 47, 48 The appearance of the p-p* shakeup satellite shows carbonization and aromatization features, which suggest good electrical conductivity of the materials.…”
mentioning
confidence: 99%
“…4a), -700 (Fig. S4a †), and -800 ( 47, 48 The appearance of the p-p* shakeup satellite shows carbonization and aromatization features, which suggest good electrical conductivity of the materials.…”
mentioning
confidence: 99%
“…To the best of our knowledge even though many studies have reported the usage of S-and N-co-doped carbonbased materials in various electrochemical applications such as supercapacitors, oxygen reduction, or water splitting (Liang et al 2012;Seredych et al 2014;Tsubota et al 2011), our research group is the irst one to address their application as gas, and speciically ammonia gas sensors (Travlou et al 2016b). To examine the ammonia sensing capability of S-and N-dual-doped nanoporous carbons, we prepared two carbon samples referred to as C-AO and C-BO (Travlou et al 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…c Dependence of ΔR/R o of the oxidized samples on the NH 3 concentrations. Copyright 2016, Elsevier (Travlou et al 2016b) Table 1 The parameters of porous structure calculated from nitrogen adsorption isotherms a Data taken from Reference (Seredych et al 2014). Copyright 2014, Elsevier (Seredych et al 2014) Sample S BET (m 2 /g) S NLDFT (m 2 /g) V t (cm 3 /g) V meso (cm 3 /g) V mic (cm 3 /g) V <0.7nm (cm 3 /g) V <1nm (cm 3 /g) V mic /V t …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations